Usefulness of Sofosbuvir and Daclatasvir combination in the treatment of HCV infection in childhood cancer patients: experience from a tertiary care hospital - Imam, Uzma; Parkash , Ait; Daryani, Nandlal; Mumtaz, Fahad (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the usefulness of Sofosbuvir-Daclatasvir combination in the treatment of hepatitis c virus infection in paediatric cancer. Method: The retrospective study was conducted at the Oncology Department of the National Institute of Child Health, Karachi, and comprised medical charts of patients who received sofosbuvir and daclatasvir from January 2018 to January 2022. Efficacy was documented by clearance of hepatitis C virus ribonucleic acid as rapid viral response, early viral response and sustained viral response at weeks 4, 12 and 24, respectively. Drug efficacy was determined by monitoring and recording adverse effects. Chemotherapy protocol for the treatment of patients concomitantly receiving direct acting antivirals was modified while looking at drug-drug interactions. The total duration of direct acting antiviral therapy was 12 weeks. Data was analysed using SPSS 24. Results: Of the 804 patients with different malignancies, 132(16.4%) were found positive for hepatitis C virus. Of them, 28(21.21%) patients were started on direct acting antivirals; 17(60.71%) boys and 11(39.28%) girls. The overall mean age was 9.93±6.12 years. The diagnosis was pre-B acute lymphoblastic leukaemia in 18(64.28%) cases, 16(57.14%) were on maintenance chemotherapy, and 18(64.28%) had genotype 1. Pre- and post-treatment mean alanine transaminase levels were 328.00±324.00IU and 36.00±29.00IU, respectively (p=0.003). Pre- and post-treatment mean serum bilirubin levels were 3.13±3.95mg/dl and 0.61±0.21mg/dl (p=0.022). Rapid viral response was achieved in 26(92.85%) children, while early viral response and sustained viral response were achieved in all 28(100%) patients. Minor side effects were noted in 4(14.28%) patients and chemotherapy was continued in all 28(100%) cases as per the designed protocol. Conclusion: The sofosbuvir-daclatasvir combination was found to be effective in hepatitis C virus treatment in paediatric cancer patients. Key Words: Childhood cancer, HCV infection, Direct acting antiviral agents.